2021
DOI: 10.1101/2021.03.24.436792
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Modular Dynamic Biomolecular Modelling with Bond Graphs: The Unification of Stoichiometry, Thermodynamics, Kinetics and Data

Abstract: Renewed interest in dynamic simulation models of biomolecular systems has arisen from advances in genome-wide measurement and applications of such models in biotechnology and synthetic biology. In particular, genome-scale models of cellular metabolism beyond the steady state are required in order to represent transient and dynamic regulatory properties of the system. Development of such whole-cell models requires new modelling approaches. Here we propose the energy-based bond graph methodology, which integrate… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 88 publications
(155 reference statements)
0
5
0
Order By: Relevance
“…Embedding bond graphs within a programmatic environment allows models to be constructed using higher-level descriptions. Previous work has shown that bond graphs can be constructed from a series of reactions [41], and further work will focus on incorporating rule-based modelling for constructing models of highly complex interactions between proteins, ligands and receptors [61].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Embedding bond graphs within a programmatic environment allows models to be constructed using higher-level descriptions. Previous work has shown that bond graphs can be constructed from a series of reactions [41], and further work will focus on incorporating rule-based modelling for constructing models of highly complex interactions between proteins, ligands and receptors [61].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a bond graph approach allows alternative rate laws to be easily swapped for one another while retaining thermodynamic consistency. It is worth noting that the Michaelis-Menten rate law can be derived as a simplification of a more complex mass action model [40,41]. In some cases, the full dynamics of the enzymatic reaction need to be considered.…”
Section: A Modular Representation For Enzymesmentioning
confidence: 99%
See 1 more Smart Citation
“…The choice of rate laws is a trade-off between "mechanisticness" on the one hand and model complexity and number of parameters on the other hand. Using a thermodynamics-based formalism [31,32] helps to create physically feasible models. Furthermore, such a parameterization can reduce the number of unknown parameters and simplify parameter estimation.…”
Section: Constructing Kinetic Modelsmentioning
confidence: 99%
“…The bond graph theory used in this paper was developed by Gawthrop and Crampin [9] and introductory material is available [21,22]. The bond graph modelling in this paper is based on the Python package [23] available at .…”
Section: Introductionmentioning
confidence: 99%